Seaweed Productivity in Warbal Village, Southeast Maluku Regency, Maluku Province - Masbaitubun, Elma Thiansi; Riry, Johan; Lasaiba, Muhammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
The Kei Islands are surrounded by small islands and the sea, which means that the lives of the people, especially seaweed farmers, are primarily dependent on the sea, especially the people of Warbal village. The sea is a place to earn a living, so you cannot be careless about the sea. The type of research used is quantitative research, supported by qualitative research. The quantitative type was carried out using a descriptive survey method, complemented by a qualitative method through in-depth interviews regarding seaweed productivity in Warbal Village. Seaweed productivity in Warbal Village has decreased due to several factors, one of which is price. The market price of seaweed has reduced dramatically; in 2022, seaweed will be IDR 30,000/kg, while in 2023, the cost of seaweed will be IDR 10,000/kg. The total production of seaweed produced by the respondent with the lowest production yield, where the total production for seven months was 203 kg, and the total production output was IDR 2,030,000, while the respondent with the highest production yield was 260 kg with the total production output being IDR .2,600,000. The low productivity of seaweed cultivation refers to the resulting production limitations that impact the income of seaweed farmers. Unexpected maximum seaweed production is also caused by repeated use of seeds, so the seeds are of low quality because they carry disease seeds, or their disease resistance has been reduced.